Dinuclear zinc(II) complexes with hydrogen bond donors as structural and functional phosphatase models - Bosch, Simone; Comba, Peter; Gahan, Lawrence R.; Schenk, Gerhard (Inorganic chemistry, 2014)
It is becoming increasingly apparent that the secondary coordination sphere can have a crucial role in determining the functional properties of biomimetic metal complexes. We have therefore designed and prepared a variety of ligands as metallo-hydrolase mimics, where hydrogen bonding in the second coordination sphere is able to influence the structure of the primary coordination sphere and the substrate binding. The assessment of a structure-function relationship is based on derivates of 2,6-bis{[bis(pyridin-2-ylmethyl)amino]methyl}-4-methylphenol (HBPMP = HL1) and 2-{[bis(pyridin-2-ylmethyl)amino]methyl}-6-{[(2-hydroxybenzyl)(pyridin-2-ylmethyl)amino]methyl}-4-methylphenol (H2BPBPMP = H2L5), well-known phenolate-based ligands for metallo-hydrolase mimics. The model systems provide similar primary coordination spheres but site-specific modifications in the secondary coordination sphere. Pivaloylamide and amine moieties were chosen to mimic the secondary coordination sphere of the phosphatase models, and the four new ligands H3L2, H3L3, HL4, and H4L6 vary in the type and geometric position of the H-bond donors and acceptors, responsible for the positioning of the substrate and release of the product molecules. Five dinuclear ZnII complexes were prepared and structurally characterized in the solid, and four also in solution. The investigation of the phosphatase activity of four model complexes illustrates the impact of the H-bonding network: the Michaelis-Menten constants (catalyst-substrate binding) for all complexes that support hydrogen bonding are smaller than for the reference complex, and this generally leads to higher catalytic efficiency and higher turnover numbers.
Gesehen am 10.09.2020